Association of serum vitamin D level with age in individuals with normal renal function - Nasri Hamid; Ardalan Mohammad-Reza (Society of Diabetic Nephropathy Prevention, 2012)
There is no sufficient data on the relation between vitamin D status and age in subjects with normal renal function. The aim of this study was to investigate the association of serum 25-hydroxy vitamin D (25[OH]D) concentrations with age of Iranian healthy individuals. The data were collected from 259 ambulant healthy medical staffs who had the inclusion criteria of the study. Fasting 25-hydroxy vitamin D level was measured. Vitamin D deficiency was defined as having a 25(OH)D concentration <25 nmol/L. The average of persons ages were 20-65 years with mean age of 34±9 years, and about 57.5% of the participants were female. The mean±SD vitamin D level of the subjects was 29±16 nmol/L (median=26 nmol/L). Also 48% of the individuals had vitamin D deficiency. In this study, there was no association between vitamin D level and gender of the participants. A significant positive correlation of age with vitamin D level was found (r =0.002). It seems that for evaluation of 25-OH-vit D status, age should be noticed.